Understanding action learning - O'Neil, Judy (Adult learning theory and practice book series., 2007)
"Drawing from such theories as Self-Directed Learning, Learning from Experience, and Transformative Learning, Understanding Action Learning provides you with a useful model that explains the four different approaches to AL, a framework for identifying which approach to use in a particular situation, and practical tools, assessments, and exercises. Through illuminating stories and examples from organizations like Pfizer, Volvo, and Chubb, which have successfully implemented Action Learning, this is the one book that will show you how to create a fulfilling, unique program for your own organization. Combining top-shelf research with real-world experience, Understanding Action Learning is a crucial resource that no educator can afford to be without."--Jacket.